2011
DOI: 10.1515/ling.2011.027
|View full text |Cite
|
Sign up to set email alerts
|

Recursion introduces a left-branching bias (where possible)

Abstract: Capitalizing upon the recursive nature of Saxon Genitives in English, this note examines the constituent structure of double Saxon Genitives such as ( he took) my sister-in-law's child's life. An analysis of 200 cases from both the spoken and the written modality reveals a distribution of 70% left branching and 30% right branching. This left-branching bias exists in the face of a general rightbranching preference in English. It is argued that left branching stems from the recursive structure of the Saxon Genit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…This result is in harmony with a previous investigation of recursive Saxon genitives (Berg 2011). Although there are almost twice as many left-branching cases in the spoken than in the written sample, this difference turns out to be non-significant (X 2 (1) = 2.2, p > 0.1).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…This result is in harmony with a previous investigation of recursive Saxon genitives (Berg 2011). Although there are almost twice as many left-branching cases in the spoken than in the written sample, this difference turns out to be non-significant (X 2 (1) = 2.2, p > 0.1).…”
Section: Resultssupporting
confidence: 89%
“…In a previous study by Berg (2011), recursive Saxon genitives were found to be susceptible to both left-and right-branching, as exemplified in (9) and (10) from the Corpus of Contemporary American English. On a more theoretical level, it will be of interest to identify the factors that underlie this frequency distribution.…”
Section: T H O M a S B E R Gmentioning
confidence: 82%
See 2 more Smart Citations
“…This combined approach allows us to examine branching direction and ordering preferences in different types of ADJPs. From a broader perspective, this study can be viewed as an extension of previous corpus work on morphological structures (Berg 2003) to the syntactic level (see also Berg 2011). This seems all the more desirable as quantitative syntactic investigations of branching direction are at a premium.…”
Section: Introductionmentioning
confidence: 99%